Hambatan dan Peluang Pembangunan Ekonomi Inklusif dan Berkelanjutan di Kawasan Kepulauan: Tinjauan Literatur Kritis - Fatimatuz Zahrah; Sri Rahayu (Jurnal Archipelago, 2025)
Inclusive and sustainable economic development is carried out to strengthen the economy of a region by maximizing its potential and still paying attention to the long-term sustainability of life. The same efforts are being made in island areas to maximize regional wealth with the aim of increasing the economic welfare of the community. This research aims to analyze the dimensions of inclusive and sustainable economic development, obstacles and opportunities for inclusive and sustainable economic development. This research is a critical literature review  by reviewing 33 articles from 2017 to 2024, and focuses on progress research on inclusive and sustainable economic development. The findings, the focus on inclusive and sustainable economic development is carried out with good and direct coordination between the government and the community, designing green economic and blue economic development, improving infrastructure and maintaining the quality of natural resources in the archipelagic region. The obstacles experienced include the readiness and quality of the community, inadequate infrastructure, lack of coordination between the government and the community, as well as poor regulations and implementation. Opportunities that were successfully analyzed were in the form of utilization of natural resource potential, an economy based on green economy and blue economy, collaboration between government and society. Full involvement from the government and good cooperation with community members and MSMEs (creative community groups) is recommended as one of the efforts to encourage inclusive and sustainable economic development in various islands and is also recommended for plans for inclusive and sustainable economic development programs.